sedinalana
1 x²=8-2x x²+2x-8=0 x1+x2=-2 U x1*x2=-8 x1=-4 U x2=2 2 -2x²=-2x-12 x²-x-6=0 x1+x2=1 U x1*x2=-6 x1=-2 U x2=3 3 -x²+2x+2=-6 x²-2x-8=0 x1+x2=2 U x1*x2=-8 x1=-2 U x2=4 4 x³-3=2x x²-2x-3=0 x1+x2=2 U x1*x2=-3 x1=-1 U x2=3 5 x²+2x-0,5=2x+2,5 x²=3 x=-√3 U x=√3
Answers & Comments
x²=8-2x
x²+2x-8=0
x1+x2=-2 U x1*x2=-8
x1=-4 U x2=2
2
-2x²=-2x-12
x²-x-6=0
x1+x2=1 U x1*x2=-6
x1=-2 U x2=3
3
-x²+2x+2=-6
x²-2x-8=0
x1+x2=2 U x1*x2=-8
x1=-2 U x2=4
4
x³-3=2x
x²-2x-3=0
x1+x2=2 U x1*x2=-3
x1=-1 U x2=3
5
x²+2x-0,5=2x+2,5
x²=3
x=-√3 U x=√3